Genetic diversity analysis in sunflower (Helianthus annuus L.) restorer lines using SSR markers: GENETIC DIVERSITY ANALYSIS IN SUNFLOWER RESTORER LINES USING SSR MARKERS - C RAMANAIAH; P KADIRVEL (Journal of Oilseeds Research, 2021)
Sunflower is a staple oilseed crop ofthe world. Genetic diversity in the parental lines is key for hybrid breeding programmes in sunflower. In this study, genetic diversity in a set of 102 parental lines (100 restorer and twoCMS) of sunflower was assessed using 69 polymorphic SSR markers. The genetic diversity parameters: average number of alleles (3.07) per locus, gene diversity (0.356) and polymorphism information content (0.296) revealed low to moderate genetic diversity in the restorer lines. The SSR marker ORS447 located on linkage group 2 was more informative with high number of alleles (10) and high PIC value (0.89). Cluster analysis (neighbour-joining tree) revealed three major genotypic groups. Model based STRUCTURE analysis showed recognizable population structure; based on membership coefficients(>80%), 82 genotypes were classified into two populations (K=2) and the remaining 20 genotypes were classified into admixture group. The Fst value (0.278) suggested that the populations were differentiated. Analysis of molecular variance resultsshowed that maximum of genetic variation (72%) was observed between the individuals within the population suggesting that the population was weakly structured. These results would be useful for selecting SSR markers for genotype characterization as well as choosing diverse parents for hybrid development programme in sunflower.